Differential effects of inhibitory G protein isoforms on G protein-gated inwardly rectifying K+ currents in adult murine atria - Nobles, Muriel (2018)
Fil: Nobles, Muriel. Barts and the London School of Medicine and Dentistry. William Harvey Research Institute. The Heart Centre; Reino Unido